Spectral Discrete Probability Density Function of Measured Wind Turbine Noise in the Far Field - Ashtiani, Payam; Denison, Adelaide (Frontiers in Public Health, 2015)
Of interest is the spectral character of wind turbine noise at typical residential set-back distances. In this paper a spectral statistical analysis has been applied to immission measurements conducted at three locations. This method provides discrete probability density functions for the Turbine ONLY component of the measured noise. This analysis is completed for 1/3rd Octave sound levels, at integer wind speeds, and is compared to existing metrics for measuring acoustic comfort as well as previous discussions on low frequency noise sources.